2016
DOI: 10.1097/aap.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Epinephrine in Caudal Anesthesia Increases Stroke Volume and Cardiac Output in Children

Abstract: Epinephrine added to local anesthetic injected for caudal anesthesia produces significant increases in SV, CO, and CI in children. Stroke volume and CI changes from epinephrine added to local anesthetic for caudal anesthesia seem to take place only in children 6 months or older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our study showed no significant difference in systolic, diastolic, and mean arterial blood pressure between the two groups. However, in our study, children receiving (2). This finding is consistent with our study showing an increase in the first-minute heart rate among children in the study group compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed no significant difference in systolic, diastolic, and mean arterial blood pressure between the two groups. However, in our study, children receiving (2). This finding is consistent with our study showing an increase in the first-minute heart rate among children in the study group compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…They did not observe any significant difference in the cardiac index and stroke volume between the epinephrine-receiving group and the control group, which is consistent with our study results in changes in heart rate and blood pressure. However, in children aged six months or more, the cardiac index and stroke volume significantly increased in the epinephrinereceiving group compared to the control group (2).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, B Cook ( 53 ) demonstrates that its analgesic effect is less pronounced than the addition of ketamine 0.5 mg/kg or clonidine 2 ug/kg to 0.25% bupivacaine on children undergoing inguinal hernia repair and circumcision. Liu's study ( 54 ) is the first to examine the effect of local anesthetic with and without epinephrine in caudal anesthesia using a noninvasive continuous cardiac output (CO) monitor in pediatric patients after the administration of a caudal block while under general anesthesia. Epinephrine added to the local anesthetic injected for caudal anesthesia produces significant increases in stroke volume (SV), cardiac index (CI), and CO in children.…”
Section: Adjuvantsmentioning
confidence: 99%
“…Both methods could provide accurate data about intravascular fluid status for mechanically ventilated patients using FTc (Flow Time Corrected) of TED and SVV (Stroke Volume Variation) of EC. Moreover, Liu et al [17] reported their experience in monitoring cardiac output with EC for patients having regional caudal anaesthesia and their response of COP changes to epinephrine. They demonstrated the clinical benefit of noninvasive EC monitoring of COP in rapid detection of COP change and response to medical intervention.…”
Section: Fig 1 Consort Flow Diagram Of the Participantsmentioning
confidence: 99%